Оцінювання параметрів а-стійких розподілів - Мережкін, Д. Г.; Соболев, В. І. (My University, 2012)
Analysis of time series with heavy tails of distributions is carried out. It is shown that models of such series may appear stable processes. We obtain esti mates of model parameters on the sample data.
Keywords: випадкова величина; індекс стійкості; непараметричний метод Хілла